Effect of multi stitched locations on high speed crushing of composite tubular structures - Rabiee, Ali; Ghasemnejad, Hessam (Elsevier, 2016)
The present paper experimentally investigates progressive energy absorption of fibre-reinforced polymer (FRP) composite tubular structures under high speed loading conditions. Various multi stitched locations are studied to find a correlation between single and multi-locations of stitches and energy absorption capabilities of composite absorbers. The through-thickness reinforcements are applied into locations of 10 mm, 20 mm, 30 mm, 10–20 m, 10–30 mm, 20–30 mm, 10–20–30 mm and 10–15–20–25–30–35 mm from top of the tubes. It is shown that multi-stitched location can cause several increase of crushing load and consequently increase of energy absorption of composite tube absorbers. The idea would be expanded to other designs which are followed by increase of stitched locations and reduction of the distance between stitches to improve the mean force with a smooth and progressive pattern of crushing load.
Keywords: Polymer-matrix composites (PMCs); Crack; Progressive; Crush; Multi-stitches